Effect of finishing/polishing techniques and low temperature degradation on the surface topography, phase transformation and flexural strength of ultra-translucent ZrO2 ceramic - Vila-Nova, Taciana Emília Leite; Gurgel de Carvalho, Isabelle Helena; Moura, Dayanne Monielle Duarte; Batista, André Ulisses Dantas; Zhang, Yu; Paskocimas, Carlos Alberto; Bottino, Marco Antonio [UNESP]; de Assunção e Souza, Rodrigo Othávio (Elsevier, 2020)
Objective: To investigate the effect of different surface finishing and polishing regimes and low temperature degradation on flexural strength, phase transformation and surface topography of ultra-translucent ZrO2 ceramic. Methods: 300 (n = 15/group) of conventional zirconia (Z: Ice Zirkon Transluzent) and ultra-translucent zirconia (UT: Prettau Anterior) bar-specimens were made and divided according to the “Finishing/Polishing” - (C — Control, B — diamond rubber polishers, P — adjusting with burs, PB — adjusting with burs + diamond polishers, PG — adjusting with burs + glaze), “Low temperature Degradation (LTD)” (with or without a treatment at 127 °C, 1.7 bar/24 h). Then, a 3-point mini flexural test was performed in a universal testing machine (1 mm/min, 500 kgf load cell). SEM, EDS, XDR, AFM, optical profilometry and Weibull analysis were performed. Data were analyzed by 3-way ANOVA and Tukey's post-test (5%). Results: Groups ZPBD (1670 ± 253 MPa), ZBD (1664 ± 217 MPa), and ZB (1655 ± 3678 MPa) showed significantly higher flexural strength than the UTPG group (372 ± 56 MPa). The Weibull modulus was significantly higher for the ZPD group compared to the UB, UCD, UPD and UPBD, while UTB, UTCD and UTPD had the lowest value. Monoclinic phases were observed only in the conventional zirconia groups and were more evident after LTD. Diamond rubber polishers presented less roughness for both zirconias. Significance: The use of diamond rubber polishers is the most suitable finishing/polishing method for zirconia ceramic restorations and that final glazing reduces the fracture resistance of these materials.
Keywords: Cubic zirconia; Dental ceramics; Monoclinic zirconia; Monolithic zirconia